2018
DOI: 10.3390/ijerph15050991
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of Regulatory Emotional Self-Efficacy on the Association between Self-Esteem and School Bullying in Middle School Students: A Cross-Sectional Study

Abstract: School bullying is negatively associated with self-esteem, but psychological mediators of bullying have yet to be clarified. We examined regulatory emotional self-efficacy (RESE) as a possible mediator in the association between self-esteem and school bullying. A cross-sectional study of 995 adolescents was conducted in two middle schools of Xi’an. All of the participants completed the Chinese version of the School Bullying Experience Questionnaire (C-SBEQ), Self-Esteem Scale (SES), and Regulatory Emotional Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 47 publications
3
33
0
Order By: Relevance
“…At the same time, they can have serious repercussions on health and social adjustment [ 14 , 48 ]. These results follow the line of other recent studies that showed the mediator role of emotional self-efficacy between peers and parents attachment and other internalizing [ 49 ] and externalizing variables [ 37 , 38 ]. Also, peer attachment is associated directly and negatively with victimization, which reinforces the importance and the role played by peer attachment in adolescence, as it facilitates experiencing and expressing positive emotions and is associated with lower victimization.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…At the same time, they can have serious repercussions on health and social adjustment [ 14 , 48 ]. These results follow the line of other recent studies that showed the mediator role of emotional self-efficacy between peers and parents attachment and other internalizing [ 49 ] and externalizing variables [ 37 , 38 ]. Also, peer attachment is associated directly and negatively with victimization, which reinforces the importance and the role played by peer attachment in adolescence, as it facilitates experiencing and expressing positive emotions and is associated with lower victimization.…”
Section: Discussionsupporting
confidence: 91%
“…In the last decades, many studies have explored the mediator role of self-efficacy and especially of emotional self-efficacy [ 24 , 36 , 37 , 38 ]. These studies brought to light, among other things, the role of emotional self-efficacy between the different variables and victimization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional and cyber bullying can have an adverse impact on the mental health of child and adolescent victims [11, 16, 17]. Both forms of bullying have been associated with depression [18], anxiety [19], low self-esteem [20], difficulties with relationships, school absenteeism [21] and substance abuse [22].…”
Section: Introductionmentioning
confidence: 99%
“…Self-efficacy includes individuals’ thoughts about their successes and failures, and their perceptions of feedback they have received. Previous studies have shown that a high degree of self-efficacy is related to higher self-belief [8], and that self-efficacy is one of the most important factors contributing to behavior change [9]. This concept was expanded upon by Schwarzer and Renner, who developed the term general self-efficacy (GSE), which is used herein [10].…”
Section: Introductionmentioning
confidence: 99%